Alemtuzumab in the treatment of fludarabine refractory B-cell chronic lymphocytic leukemia (CLL) - Marco Montillo (Dove Medical Press, 2008)
Marco Montillo, Francesca Ricci, Sara Miqueleiz, Alessandra Tedeschi, Enrica MorraDepartment of Oncology/Hematology, Division of Hematology and Bone Marrow Transplant Unit, Niguarda Ca’ Granda Hospital, Milan, ItalyAbstract: The introduction of immunotherapeutic agents has provided renewed hope for Chronic lymphocytic leukemia fludarabine-refractory patients. Several clinical trials have shown that alemtuzumab is a more effective option compared to combination chemotherapy for treatment of patients who have relapsed or who are refractory to fludarabine, including those with poor prognostic factors. Although there are significant potential toxicities associated with alemtuzumab, such as infusional reactions and the risk of cytomegalovirus (CMV) reactivation, most are manageable. Pre-treatment anti-pyretics and anti-histamines are recommended to prevent or mitigate the acute infusional reactions associated with intravenous infusion. Recent use of alemtuzumab via the subcutaneous route has been shown to be well tolerated and has yielded similar response rates to the infusional method of administration. Prophylaxis with thrimethoprim/sulphamethoxazole (TMP/SMZ) as well as valacyclovir or a similar anti-viral can prevent many of the opportunistic infections seen in early trials. Reactivation of CMV infection can be effectively managed with monitoring and early treatment. Chemo-immunotherapy combination with alemtuzumab has been tested and demonstrated unprecedented clinical results in relapsed and refractory patients. The use of this agent earlier in the algorithm of patients with these characteristics should be considered. Future areas of research will include the use of alemtuzumab in combination with other monoclonal antibodies and other targeted therapies.Keywords: chronic lymphocytic leukemia, fludarabine, alemtuzumab